Immediate implant in aesthetic area with digital flow: Clinical case report and 2-year floow-up (Research, Society and Development, 2024)
The immediate dental implant surgical technique combined with immediate dental implant loading and digital workflow has revolutionized the implantology offering rapid and efficient solution for mouth rehabilitation. The dental implants require a wound healing period that can cause anxiety for the patient. Furthermore, by using this technique, the dental implants can be installed immediately after the tooth extraction and receive the dental implant loading at the same which favors the wound healing, reducing the duration of the treatment. In turn, the digital workflow incorporates new technologies such as CEREC CAD/CAM system that enable the digital planning cases and the manufacturing of high-quality prosthetic crowns. The chairside concept, CEREC, enables indirect esthetic restorations to be carried out in a single session inside the dental office. Clinical studies showed that the digital workflow enabled the production of indirect esthetic restorations that presented exceptional clinical survival rate. The present study reviews the literature and discloses the clinical case of a patient submitted to immediate implant surgery and dental implant loading, rehabilitated by the use of the digital workflow, assisted by the CEREC CAD/CAM system.